2016
DOI: 10.1371/journal.pone.0160705
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study of the Permeability and Uptake of Mesoporous Silica Nanoparticles across the Blood-Brain Barrier

Abstract: Drug delivery into the brain is impeded by the blood-brain-barrier (BBB) that filters out the vast majority of drugs after systemic administration. In this work, we assessed the transport, uptake and cytotoxicity of promising drug nanocarriers, mesoporous silica nanoparticles (MSNs), in in vitro models of the BBB. RBE4 rat brain endothelial cells and Madin-Darby canine kidney epithelial cells, strain II, were used as BBB models. We studied spherical and rod-shaped MSNs with the following modifications: bare MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 41 publications
2
58
1
Order By: Relevance
“…36 Preliminary reports suggest that SiNPs are capable of crossing the blood-brain barrier, making them potentially attractive agents for glioblastoma treatment. [37][38][39][40] Moreover, Ducray et al showed that two sets of modified SiNPs (Si-indocyanine green/polycaprolactonepolylactic acid-rhodamine-doped and indocyanine green/ polycaprolactone-rhodamine-doped NPs) did not impair cell viability or induce neuroinflammation in primary hippocampal cultures. 41 Additionally, animal models have demonstrated the biocompatibility and relative safety of SiNPs for in vivo use in mice and rats.…”
Section: Discussionmentioning
confidence: 99%
“…36 Preliminary reports suggest that SiNPs are capable of crossing the blood-brain barrier, making them potentially attractive agents for glioblastoma treatment. [37][38][39][40] Moreover, Ducray et al showed that two sets of modified SiNPs (Si-indocyanine green/polycaprolactonepolylactic acid-rhodamine-doped and indocyanine green/ polycaprolactone-rhodamine-doped NPs) did not impair cell viability or induce neuroinflammation in primary hippocampal cultures. 41 Additionally, animal models have demonstrated the biocompatibility and relative safety of SiNPs for in vivo use in mice and rats.…”
Section: Discussionmentioning
confidence: 99%
“…Given the fact, that MSNs have been recognized for their role in delivering therapeutic drugs for various diseases, in the year 2016, Baghirov et al investigated the uptake, transport, and cytotoxicity of MSN based drug nanocarriers functionalized with PEG–PEI block copolymer using in vitro models of the BBB . They used RBE4 rat brain endothelial cells, as well as Madin–Darby canine kidney epithelial cells for their experiments, as given in Figure .…”
Section: Crossing the Blood–brain Barriermentioning
confidence: 99%
“…d) Scanning electron microscopy micrograph of rod‐shaped MSNs. Reproduced under the terms and conditions of the Creative Commons Attribution License . Copyright 2016, Baghirov et al, published by Plos.…”
Section: Crossing the Blood–brain Barriermentioning
confidence: 99%
“…New methods of powder preparation have recently been described for various biomedical applications aiming to control the particle size, the morphological characteristics, as well as encapsulation efficiency [ 28 , 29 , 30 ]. The association of drugs with micro- and nanoparticle carrier systems has allowed to overcome the challenges in the development of inhaled therapeutic systems [ 27 , 31 , 32 , 33 ], and to modulate the drug release profiles [ 34 , 35 ]. Another important point to consider is the ability of the particles to circunvent the mechanisms of defense of the lung against foreign substances, besides being non-toxic and biocompatible (20).…”
Section: Introductionmentioning
confidence: 99%